Dr. Tiia Pihlamaa — Deep Plane Facelift — Helsinki - Pihlamaa, Tiia (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Tiia Pihlamaa, practicing in Helsinki, Finland. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003337; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; finland; helsinki